2013
DOI: 10.1111/jonm.12095
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric palliative care: a review of needs, obstacles and the future

Abstract: Nursing management plays a crucial role in addressing the clinical, operational and financial needs and concerns that are grounded in paediatric palliative care literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
0
13
0
3
Order By: Relevance
“…6 The main reported barriers in paediatric palliative care as experienced by healthcare providers are communication, the uncertainty of the prognosis, time constraints and lack of education. [7][8][9][10][11] Studies on barriers experienced by parents show that communication is a major barrier for them. [12][13][14][15][16][17] Other frequently mentioned barriers are a lack of care for the family 12 13 and bereavement care.…”
Section: Introductionmentioning
confidence: 99%
“…6 The main reported barriers in paediatric palliative care as experienced by healthcare providers are communication, the uncertainty of the prognosis, time constraints and lack of education. [7][8][9][10][11] Studies on barriers experienced by parents show that communication is a major barrier for them. [12][13][14][15][16][17] Other frequently mentioned barriers are a lack of care for the family 12 13 and bereavement care.…”
Section: Introductionmentioning
confidence: 99%
“…The PaPaS promotes greater clarity and effective handover for everyone involved, particularly at care transitions. This can lead to important outcomes like alignment of expectations No (2) between stakeholders, and critically, optimal case management. Ultimately, the child and family living with lifeshortening illness is flagged in a timely manner to receive palliative care based on needs rather than prognosis, in spite of challenges posed by disease diversity and uncertain trajectories, through a process of screening that is both robust and informational, yet with cost-containing implications.…”
Section: Resultsmentioning
confidence: 99%
“…Author details 1 HCA Hospice Care, 705 Serangoon Road, #03-01 Block A @ Kwong Wai Shiu Hospital, Singapore 328127, Singapore. 2 Ministry of Health Holdings, Singapore, Singapore.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is true of adult services, the situation in pediatric palliative care services is different. [ 16 ] Another study found that 68% of volunteers were involved in counselling and volunteers in 42% of organizations belonged to mental health profession. [ 14 ] In a randomized controlled trial, senior volunteers were useful in delivering a reminiscence and creative activity intervention.…”
Section: Introductionmentioning
confidence: 99%